Human-Centric Management: Nurturing Talent, Building Culture, and Driving Organizational Success - Olivia Hector; Rory Cameron (International Journal of Science and Society, 2023)
This journal article, titled "Human-Centric Management: Nurturing Talent, Building Culture, and Driving Organizational Success," explores the pivotal role of human-centric management in modern organizations. Through a comprehensive literature review and qualitative analysis, it examines the evolving concept of human-centric management, tracing its historical development and contemporary significance. The article delves into the intricate relationship between talent management, organizational culture, and overall organizational success, drawing upon relevant theories and frameworks to illuminate key insights. Furthermore, it highlights the importance of aligning talent management practices and cultural factors with organizational strategy and identifies critical gaps in the existing literature. By shedding light on the multifaceted dynamics of talent, culture, and success, this article aims to equip practitioners and scholars with actionable insights to foster human-centric management practices that drive organizational excellence.